EXPERIENCE OF ADMINISTRATION OF SOLUBLE RECEPTORS TO TNF-α IN PATIENT WITH SEVERE POLYARTICULAR TYPE OF JUVENILE RHEUMATOID ARTHRITIS - T.M. Bzarova; E.I. Alexeeva; S.I. Valieva; R.V. Denisova; A.O. Lisitsyn; N.А. Tsurikova (Вопросы современной педиатрии, 2010)
The article presents a case report of early debut and severe clinical course of polyarticular type of juvenile rheumatoid arthritis which was refractory to the treatment with classical immunosuppressants and secondary inefficiency of chimeruc monoclonal antibodies to tumor necrotizing factor (TNF). Authors described successful administration of soluble receptors to TNF — etanercept in dose 0,4 mg/kg of body weight. Patient receives etanercept during 12 weeks. In 4 weeks after the onset of treatment there was lessening of painfulness and exudative alterations of joints, increase of range of motions in them. The quality of life of child and child’s family significantly improved in 3 months of treatment.Key words: children, juvenile rheumatoid arthritis, etanercept, treatment.(Voprosy sovremennoi pediatrii — Current Pediatrics. – 2010;9(3):88-96)